Toxicity, Antimicrobial Activity and Detection of Xanthones in Gentianella Nevadensis - Hidalgo Báez, Doris; Quintero, Maribel; Nieves, Beatriz; De los Ríos, Carmen; Contreras, Quilianio; Estrada, Javier (Ciencia, 1970)
The species Gentianella nevadensis (Gilg) Weaver & Rudenberg (Gentianaceae), is known as “dictamo real” in Mérida where a legend is found which speaks about its rejuvenation attribute. A decoction or an alcoholic beverage of the roots and aerial parts of G. nevadensis is used as a tonic, analgesic, to regulate the circulation, as an aphrodisiac and as a stomachic. This plant was screened for toxicity using the brine shrimp: Artemia salina bioassay and antimicrobial activity. The detection of xanthones was also carried out by HPLC coupled with a UV photodiodearray. All crude extracts except the ethanol ones showed a low toxicity against Artemia salina. The highest toxicities were observed in some fractions of dichloromethane and ethyl acetate extracts. Ethyl acetate extract and its fractions were the only ones with antibacterial activity against Staphylococcus aureus and Bacillus subtilis. Xanthones were detected in dichloromethane and ethyl acetate extracts and their fractions. Bellidifolin and desmethylbellidifolin were isolated, both have been reported as inhibitors of MAO. The results of this study suggest that G.nevadensis could be a possible antidepressive and anti-infectious agent.